Assessment and Study of Types of Finish Lines in Tooth Preparation - An Observational Study - Vigneshwaran Ravichandran1 , Manjari Chaudhary2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
The fixed and removable prosthodontics aims at the maintenance and preservation of the tooth structure .Restoration of teeth is possible only if sufficient space is created for the application of thickness of materialrequired . The types of finish lines given for all ceramic , metal ceramic and all metallic tooth preparationsare Chamfer , Shoulder finish line, etc , The aim of this observational study is to assess the different types offinish lines given in the tooth preparation . The study is focused to assess the different types of finish linesin tooth preparation and to assess the most preferred type of finish line as the tooth margin . Around 1000different tooth preparations were observed to assess the types of finish lines . The data was obtained from86,000 archived patient records . All the collected data were reviewed and statistically analysed . In thepresent study , most of the patients were 31 to 45 yrs old (42 %) . Among the patients , 56% were Male .Majority of the tooth preparations were done in Sextant 2 (35%) . The most preferred type of finish line wasthe Shoulder finish line (77 %).The study has observed that the shoulder finish line was the most preferredtype of finish line .